Research handbook on economic sanctions - Bergeijk, Peter A. G. van, 1959-; Ledda, Gina Macatangay (Cheltenham ; Northampton : Edward Elgar Publishing, 2021)
Peter van Bergeijk brings together 40 leading experts from all continents to analyze state-of-the-art data covering the sharp increase in (smart) sanctions in the last decade. Original chapters provide detailed analyses on the determinants of sanction success and failure, complemented with innovative research on the impact of sanctions. This timely Research Handbook provides both a thorough discussion of methodology as well as evidence-based policy advice on the efficient application of boycotts, embargoes, and targeted sanctions, including trade, travel and financial sanctions. The use of case studies from Cuba, Iran, North Korea and Russia illustrate developments and demonstrate new methods, including stochastic frontier analysis, comparative quantitative analysis and meta-analysis. Providing crucial information, this Research Handbook will be an excellent resource for academic researchers in international political economy and international relations as well as policy makers within national and global institutions. It will also provide obligatory reading for students also studying within these fields.
Publikace přináší ucelený přehled současného výzkumu ekonomických sankcí jako nástroje zahraniční politiky. Na základě spolupráce čtyřiceti odborníků z různých kontinentů kniha analyzuje příčiny úspěchu a neúspěchu sankčních opatření, jejich dopady na ekonomiku a mezinárodní vztahy, a představuje nové metodologické přístupy včetně stochastické hraniční analýzy či metaanalýzy. Na konkrétních příkladech (Kuba, Írán, Severní Korea, Rusko) autoři ukazují dynamiku moderních „chytrých“ sankcí a jejich místo v mezinárodním právu a politické ekonomii.
Částečně tištěno napříč
Poznámky
Obsahuje bibliografické odkazy a rejstřík
Keywords: 21. století; hospodářské sankce; mezinárodní právo; mezinárodní hospodářské vztahy; geopolitika; ekonomická diplomacie; sankce v mezinárodním právu; studie; sborníky; 21st century; economic sanctions; international law; international economic relations; geopolitics; economic diplomacy; sanctions (international law); studies